Evaluasi Implementasi 7 Kebiasaan Anak Indonesia Hebat pada Madrasah di Kalimantan Timur dalam Aspek Politik, Ekonomi, Sosial, dan Budaya - Arini Hasanah; Suprihartini; Warman; Mohammad Bahzar; Nurlaili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the implementation of the Seven Habits of Great Indonesian Children (7KAIH)program in madrasahs across East Kalimantan by examining four key dimensions: political, economic, social, and cultural. The program is designed to cultivate students’ superior character, independence, and social awareness, aligning with Indonesia’s human resource development agenda to enhance global competitiveness. The research employed a quantitative-descriptive evaluative approach using the CIPP (Context, Input, Process, Product) model. Data were collected from teachers, principals, and parents in five madrasahs: MIN 1 Samarinda, MIN 2 Balikpapan, MTsN 1 Tenggarong, MAN 2 Bontang, and MAN IC Paser. The findings indicate that the overall implementation level of the program falls under the “good” category, with an average score of 83.6%. The social and cultural dimensions achieved the highest score (86.4%), followed by the economic (82.7%) and political (81.8%) dimensions. Policy implications emphasize strengthening the role of madrasahs as agents of national character formation, integrating character education into regional policies, and providing sustained economic and social support to ensure long-term program implementation.